Paediatric trauma systems and their impact on the health outcomes of severely injured children: protocol for a mixed methods cohort study - Curtis, Kate (2016)
Background: Injury is a leading cause of death and disability for children. Regionalised trauma systems have improved outcomes for severely injured adults, however the impact of adult orientated trauma systems on the outcomes of severely injured children remains unclear. The objective of this study is to review the processes of care and describe the impacts of a regionalised trauma system on the outcomes of severely injured children. Methods: This article describes the design of a mixed methods cohort study evaluating the paediatric trauma system in New South Wales (NSW), the most populous state in Australia. Recommendations and an implementation strategy will be developed for aspects of the paediatric trauma care system that require change. All injured children (aged <16 years) requiring intensive care, or with an Injury Severity Score (ISS) ≥ 9 treated in NSW, or who died following injury in NSW in the 2015–16 financial year, will be eligible for participation. Injury treatment and processes will be examined via retrospective medical record review. Quality of care will be measured via peer review and staff interviews, utilising a human factors framework. Health service and cost outcomes will be calculated using activity based funding data provided by the Ministry of Health. Health-related quality of life (HRQoL) proxy measures will occur at baseline, 6 and 12 months to measure child HRQoL and functional outcomes. Discussion: This will be the first comprehensive analysis undertaken in Australia of the processes and systems of care for severe paediatric injury. The collaborative research method will encourage clinician, consumer and clinical networks to lead the clinical reform process and will ultimately enable policy makers and service providers to ensure that children seriously injured in Australia have the best opportunity for survival, improved functional outcome and long-term quality of life.